Development of editorial models applying augmented reality for children's learnin - Borja-Galeas, Carlos (2019)
The content of a written document is organized in a coherent, aesthetic and harmonious manner with the principles of editorial design. If it uses augmented reality, one of the new technologies must also be taken into account when generating the composition. In the present article we present a model of editorial design with augmented reality focused on influencing the learning process of middle-aged children. Its construction will be based on the golden ratio, the Fibonacci succession, following the Vignelli canon. The results will allow improving the model to develop future research projects.